Geographic structure and host specificity shape the community composition of symbiotic dinoflagellates in corals from the Northwestern Hawaiian Islands - Stat, Michael; Yost, D.; Gates, R. (Springer, 2015)
How host–symbiont assemblages vary over space and time is fundamental to understanding the evolution and persistence of mutualistic symbioses. In this study, the diversity and geographic structure of coral–algal partnerships across the remote Northwestern Hawaiian Islands archipelago was investigated. The diversity of symbionts in the dinoflagellate genus Symbiodinium was characterised using the ribosomal internal transcribed spacer 2 (ITS2) gene in corals sampled at ten reef locations across the Northwestern Hawaiian Islands. Symbiodinium diversity was reported using operational taxonomic units and the distribution of Symbiodinium across the island archipelago investigated for evidence of geographic structure using permutational MANOVA. A 97 % sequence similarity of the ITS2 gene for characterising Symbiodinium diversity was supported by phylogenetic and ecological data. Four of the nine Symbiodinium evolutionary lineages (clades A, C, D, and G) were identified from 16 coral species at French Frigate Shoals, and host specificity was a dominant feature in the symbiotic assemblages at this location. Significant structure in the diversity of Symbiodinium was also found across the archipelago in the three coral species investigated. The latitudinal gradient and subsequent variation in abiotic conditions (particularly sea surface temperature dynamics) across the Northwestern Hawaiian Islands encompasses an environmental range that decouples the stability of host–symbiont assemblages across the archipelago. This suggests that local adaptation to prevailing environmental conditions by at least one partner in coral–algal mutualism occurs prior to the selection pressures associated with the maintenance of a symbiotic state.